Attitude of executive towards in servive training programs : a case study of statutory corporations in Sarawak - Jaddil @ Zaidel, Bin Ibrahim. (2002)
The major aim of this study is to determine the general attitude of executives from selected statutory corporation in Sarawak towards in-service training programs. Another important aspect of the study is to identify factors affecting their attitudes.